DEWATS dissemination in Vietnam: achievements and lessons learnt - Nguyen T. Phong; Vu Hai Nam; Pham Thi Hai Yen (2014)
The speedy economic development and rapid growth of population and urbanization in Vietnam have created great pressure on the environment by its manufacturing process and human activities. Thus, it is necessary to protect the environment through policies and appropriate technology for the sustainable development of the country. The DEcentralized WAstewater Treatment Solutions (DEWATS) dissemination in Vietnam is one of the measures contributing to address this issue.